The Subtlety of Sound: Accent as a Marker for Culture. (June 2015) - Dehghani, Morteza; Khooshabeh, Peter; Nazarian, Angela; Gratch, Jonathan
Aspects of language, such as accent, play a crucial role in the formation and categorization of one's cultural identity. Recent work on accent emphasizes the role of accent in person perception and social categorization, demonstrating that accent also serves as a meaningful indicator of an ethnic category. In this article, we investigate whether the accent of an interaction partner, as a marker for culture, can induce cultural frame-shifts in biculturals. We report the results of three experiments, performed among bicultural and monocultural individuals, in which we test the above hypothesis. Our results demonstrate that accent alone can affect people's cognition.